Prevalence and characteristics of smoking cigarette and narghile among Syrian refugee parents in Ontario, Canada. - Hala Tamim; Aliya Beyhum; Aseel Alzaghoul; Durmalouk Kesibi; Baraa Alghalyini; Khalid Yunis (Public Library of Science (PLoS), 2024)
This study aimed to explore the prevalence and associated sociodemographic, migration, and health-related factors of smoking cigarettes and narghile among Syrian refugee parents resettled in Ontario, Canada since 2015. A total of 540 Syrian refugee parents, with at least one child less than 18 years of age, were interviewed. Multivariate logistic regression analysis was performed to assess the independent relationship between each of the associated sociodemographic, migration, and health-related factors and smoking cigarettes and narghile. The overall prevalence of smoking was 43% (cigarette = 22%, narghile = 25.6%). The average number of cigarettes smoked per day was 15.4 (SD = 10.1). With regard to smoking narghile, 18.2% of the sample smoked daily, while 35.5% and 52.9% smoked at least once weekly and occasionally, respectively. Results from multivariate logistic regression analysis showed that more fathers were at increased odds of smoking cigarettes than mothers OR (95% CI) = 6.6 (3.7-11.9), while no such difference was found for narghile smokers OR (95% CI) = 1.5 (0.9-2.6). Results showed that smoking cigarettes was associated with lower education levels and being Muslim, whereas smoking narghile was associated with younger age and alcohol use. Poor perceived mental health was significant/approached significance for both types of smoking. Greater understanding of smoking patterns of resettled refugees is needed to direct healthcare providers to offer targeted interventions for those who are most at risk.